A partial structural and functional rescue of a retinitis pigmentosa model with compacted DNA nanoparticles. - Xue Cai; Zack Nash; Shannon M Conley; Steven J Fliesler; Mark J Cooper; Muna I Naash (PLoS ONE)
Previously we have shown that compacted DNA nanoparticles can drive high levels of transgene expression after subretinal injection in the mouse eye. Here we delivered compacted DNA nanoparticles containing a therapeutic gene to the retinas of a mouse model of retinitis pigmentosa. Nanoparticles containing the wild-type retinal degeneration slow (Rds) gene were injected into the subretinal space of rds(+/-) mice on postnatal day 5. Gene expression was sustained for up to four months at levels up to four times higher than in controls injected with saline or naked DNA. The nanoparticles were taken up into virtually all photoreceptors and mediated significant structural and biochemical rescue of the disease without histological or functional evidence of toxicity. Electroretinogram recordings showed that nanoparticle-mediated gene transfer restored cone function to a near-normal level in contrast to transfer of naked plasmid DNA. Rod function was also improved. These findings demonstrate that compacted DNA nanoparticles represent a viable option for development of gene-based interventions for ocular diseases and obviate major barriers commonly encountered with non-viral based therapies.